Aromaterapi Greentea Untuk Mengatasi Dismenorea Primer Pada Mahasiswi Program Studi S1 Ilmu Keperawatan Universitas Karya Husada Semarang - Witri Hastuti; Cicilia Ester Novita Herawati Bunga; Shindi Hapsari; Mardiyani Mardiyani (PENA NURSING, 2023)
Background: Dysmenorrhoea is an annoying pain during menstruation. The pain caused is uncomfortable, the discomfort felt if not resolved will affect the mental and physical function of the individual. Management of dysmenorrhoea can be done in two ways, namely with pharmacological therapy and non-pharmacological therapy. One of the non-pharmacological therapies is greentea aromatherapy. Aromatherapy can be used as an alternative to reduce pain levels. Objective: Knowing the effect of greentea aromatherapy on the intensity of primary dysmenorrhoea in female students of the undergraduate nursing science programme at Karya Husada University Semarang. Methods: This type of research is quantitative with pre-experimental. The research design used the one group pretest-posttest design approach with a total sample size of 30: Based on the results of the Wilcoxon test obtained a p-value of p = 0.000, which means the p value <0.05 Conclusion: There is an effect of greentea aromatherapy on primary dysmenorrhoea in female students of the S1 Nursing Science study programme at Karya Husada University Semarang.